IMPLEMENTASI MODEL PEMBELAJARAN PORTOFOLIO DALAM MENINGKATKAN MUTU PEMBELAJARAN PENDIDIKAN AGAMA ISLAM - dodi setiabudi (Pergunu Jawa Barat, 2022)
This research aims to implement the portfolio learning model to improve the quality of Islamic education learning at SMA Negeri 2 Majalaya, Bandung district. Implementation of the portfolio learning model, which includes preliminary activities, core activities and closing activities, (3) Assessment of the performance of the portfolio learning model conducted by SMA Negeri 2 Majalaya teachers, Bandung district is directed at three domains (domains) which include the cognitive, psychomotor, and affective domains, (4) Supporting factors include human resources, representative infrastructure (facilities and infrastructure), increased learning motivation. Meanwhile, the inhibiting factor in implementing the portfolio learning model is a matter of time and cost. Based on the research results obtained from the initial stage, which continues to increase, it can be concluded that the application of the portfolio learning model in PAI learning has an impact on improving the quality of student learning outcomes. The portfolio learning model is one of the learning models full of activities that foster an enthusiastic attitude for students and is a fun learning process that has been proven to increase mastery of PAI material concepts, especially on the final day. Kata Kunci: Kurikulum; Program Studi; Program MBKM